Combined Use of Lachancea thermotolerans and Schizosaccharomyces pombe in Winemaking: A Review - Benito, Santiago (Microorganisms, 2020)
The combined use of Lachancea thermotolerans and Schizosaccharomyces pombe is a new winemaking biotechnology that aims to solve some modern industrial oenology problems related to warm viticulture regions. These areas are characterized for producing musts with high levels of sugar that can potentially be converted into wines with elevated ethanol contents, which are usually associated with high pH levels. This biotechnology was reported for the first time in 2015, and since then, several scientific articles have been published regarding this topic. These reported scientific studies follow an evolution similar to that performed in the past for Saccharomyces cerevisiae and Oenococcus oeni; they start by reporting results for basic winemaking parameters at the beginning, later continuing with more advanced parameters. This review compares the results of different researchers that have applied this new biotechnology and have studied wine quality parameters such as ethanol, glycerol, malic acid, lactic acid, amino acids, aroma compounds, or anthocyanins. It is shown that the new biotechnology is repeatedly reported to solve specific winemaking problems such as the lack of acidity, biogenic amines, ethyl carbamate, or undesirable color losses. Such results highlight this biotechnology as a promising option for warm viticulture areas.